(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: This study was designed to inspect the effectiveness of a comparative study on Russian Current Stimulation versus Faradic Current in pain and functional outcome in osteoarthritis knee. Russian current is the most commonly used electrical stimulation to improve muscle strength. Faradic current is effective in treating muscle spasms caused by inflammation and in lowering pain Purpose: To compare the effectiveness of Russian current stimulation versus Faradic current using the KOOS scale. Materials and Methods: This experimental study has been conducted from November 2022 to April 2023.A total of 196 adults were collected from APR physiotherapy center with OA knee have been selected using the inclusion and exclusion criteria. They have been split into 2 groups Group A (n=98) and Group B (n=98) were assigned. Group A got Russian current stimulation, whereas Group B received Faradic current and the KOOS scale was used to evaluate the subjects. The treatments were given for 5 sessions per week and continued for 4 weeks. Results: The mean value of Russian current at the post-test was found to be higher than the mean value of Faradic current with a p-value of <0.0001. Conclusion: The result suggests that Russian current stimulation shows a significant effect in reducing pain in the OA knee when compared to Faradic current.